Professionals' views and experiences in supporting decision-making involvement for people living with dementia. (January 2021) - Sinclair, Craig; Bajic-Smith, Julie; Gresham, Meredith; Blake, Meredith; Bucks, Romola S; Field, Sue; Clayton, Josephine M; Radoslovich, Helen; Agar, Meera; Kurrle, Susan
Background: The provision of supported decision-making for people living with disabilities is an emerging area of practice and rights-based law reform, and is required under international law. Objectives: This qualitative study aimed to understand how Australian health and legal professionals conceptualised their professional roles in the practice of providing decision-making support for people living with dementia. Methods: The methods were informed by grounded theory principles. In-depth, semi-structured interviews were conducted with 28 health and legal professionals involved in providing care or services for people with dementia. Interviews explored how professionals described their practice of providing support for decision-making and how they conceptualised their roles. The analysis was underpinned by the theoretical perspective of symbolic interactionism. Results: Participants described providing support across a range of decision domains, some of which were specific to their professional role. Four key themes were identified: 'establishing a basis for decision-making', 'the supportive toolbox', 'managing professional boundaries' and 'individualist advocacy versus relational practice'. Participants identified a range of generic and specialised techniques they used to provide support for people with dementia. These techniques were applied subject to resource limitations and perceived professional obligations and boundaries. A continuum of professional practice, ranging from 'individualist advocacy' to 'relational practice' describes the approaches adopted by different professionals. Discussion: Professionals conceptualised their role in providing support for decision-making through the lens of their own profession. Differences in positioning on the continuum of 'individualist advocacy' through to 'relational practice' had practical implications for capacity assessment, engaging with persons with impaired decision-making capacity, and the inclusion of supporters and family members in decision-making processes. Further progress in implementing supported decision-making (including through law and policy reform) will require an understanding of these inter-professional differences in perceived roles relating to the practice of providing decision-making support.